Mathematical Modelling of Residual Effects of Distillery Effluents Application by Finite Difference Method - Devkota, Jyoti U.; Aryal, Sabita (Kathmandu University Journal of Science, Engineering and Technology, 2006)
Mathematical Modelling has immense applications in various fields ranging from biomedical sciences to environmental sciences. Here, mathematical modelling has been applied to an environmental pollution, in particular soil pollution problem. Finite difference method has been successfully used to predict the residual effect of potassium (K), an important component of poly-methanated effluents. Further various parameters of the soil such as electro conductivity, pH etc. have been analysed mathematically. Their inter-relationships have also been studied.